DIGITALIZATION AS A REVOLUTION IN MANAGEMENT - L. Ivanovskaya (Вестник университета)
A new opportunities in managing large, complex and dynamic social systems of individual countries and regions as well as managing economic, political and information systems of the whole world has been investigated. In general, their historical emergence as a result of the «information revolution», digital economy and digitalization of social life has been considered. Such technologies serve as a foundation of ambitions of different classes and elites to monopolize the power, which is a danger to the human society. However, this opens other prospects like creating the social justice» society. These two tendencies have been analyzed briefly in the article. The problem of our society’s class structure also from a theoretical standpoint has been reviewed.